Procedural Justice or Substantive Justice: Review of Constitutional Court Decision Number: 91/Puu/Xviii/2020 - Samuel Hamonangan Simanjuntak; Lita Tyesta A.L.W. (Badan Strategi Kebijakan Hukum, 2022)
The formal test application of the Omnibus Law of Job Creation through the Constitutional Court Decision Number:91/PUU-XVIII/2020, in its statement the Constitutional Court declared its unconstitutional conditional. The Constitutional Court decision was made because considering the need to balance the formal and the strategic objectives of the establishment of the Job Creation Law, the formal condition is procedural justice while the strategic objective is substantive justice. The decision raised the question of whether the verdict was oriented to procedural justice or substantive justice. Research question of the study was what is the Orientation of Justice of the Constitutional Court Decision Number:91/PUU-XVIII/2020? This study is on normative law research. The postpositvism paradigm used a qualitative approach through the in concreto study of and court behaviour. The results of the study are the Constitutional Court Decision Number:91/PUU-XVIII/2020 through its considerations, opinions and verdicts in the main application oriented to procedural justice. It can be concluded that The Decree of Constitutional Court Decision Number:91/PUU-XVIII/2020 is oriented to procedural justice. The study recommends, in line with the principle of justice of John Rawls, the basic legal values of Gustav Radbruch and the social justice value of Pancasila and the 1945 Constitution of the Republic of Indonesia, formal test on Omnibus Law of Kob Creation should have been rejected, and made substantive justice orientation of the Constitutional Court Decision Number:91/PUU-XVIII/2020.